2017
DOI: 10.1161/jaha.117.006959
|View full text |Cite
|
Sign up to set email alerts
|

Short Sleep Duration, Obstructive Sleep Apnea, Shiftwork, and the Risk of Adverse Cardiovascular Events in Patients After an Acute Coronary Syndrome

Abstract: BackgroundIt is unknown whether short sleep duration, obstructive sleep apnea, and overnight shift work are associated with the risk of recurrent cardiovascular events in patients after an acute coronary syndrome.Methods and Results SOLID‐TIMI 52 (The Stabilization of PLaques UsIng Darapladib‐Thrombolysis in Myocardial Infarction 52 Trial) was a multinational, double‐blind, placebo‐controlled trial that enrolled 13 026 patients ≤30 days of acute coronary syndrome. At baseline, all patients were to complete the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 46 publications
1
61
0
3
Order By: Relevance
“…We recommend using orange-tinted goggles during the commute home and wide-spectrum blue lights during work hours to promote wakefulness. We also recommend increasing 37 Other sleep disorders, such as restless legs…”
Section: Lightmentioning
confidence: 99%
“…We recommend using orange-tinted goggles during the commute home and wide-spectrum blue lights during work hours to promote wakefulness. We also recommend increasing 37 Other sleep disorders, such as restless legs…”
Section: Lightmentioning
confidence: 99%
“…With a series of eligible compounds available at present, scientists would be admired if they exerted more effort in exploring the role of Lp‐PLA2 in diseases other than atherosclerosis, particularly, in microvascular diseases that may be more sensitive to Lp‐PLA2 inhibition. In addition, the large pool of data generated from clinical trials provides numerous opportunities for comprehensive data mining, which may be beneficial to understanding the biological consequences of Lp‐PLA2 inhibition and help us to learn a profound and valuable lesson from the failure of darapladib . To conclude, we anticipate that the story of Lp‐PLA2 will continue.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…In addition, the large pool of data generated from clinical trials provides numerous opportunities for comprehensive data mining, which may be beneficial to understanding the biological consequences of Lp-PLA2 inhibition and help us to learn a profound and valuable lesson from the failure of darapladib. [279][280][281][282][283][284][285][286][287][288] To conclude, we anticipate that the story of Lp-PLA2 will continue.…”
mentioning
confidence: 98%
“…This study suggested that food content and timing, as well as eating duration, differed according to place of living, which in turn may be linked to lifestyle.Nutrients 2020, 12, 375 2 of 15 melatonin timing compared to the non-exposed group. In addition, there is evidence that urbanization and access to electricity may be associated with increased body weight and related comorbidities due to desynchronization of circadian rhythms [7,8] and insufficient sleep duration [9][10][11][12].The increase in comorbidities due to prolonged wakefulness may be exacerbated by the extension of feeding at inappropriate times for the physiological and metabolic processes regulated by the circadian timing system [13]. This scenario appears to be worse when associated with shift work [14,15].…”
mentioning
confidence: 99%
“…Nutrients 2020, 12, 375 2 of 15 melatonin timing compared to the non-exposed group. In addition, there is evidence that urbanization and access to electricity may be associated with increased body weight and related comorbidities due to desynchronization of circadian rhythms [7,8] and insufficient sleep duration [9][10][11][12].…”
mentioning
confidence: 99%